THE EFFECT OF FRIENDS SOCIAL SUPPORT OF PRIVATE VOCATIONAL SCHOOLS (ANDIKPAS) AND SELF ESTEEM ON FUTURE ORIENTATION IN THE FIELD OF WORK ON ANDIKPAS IN BANDUNG CLASS III CHILDREN'S PRIVACY INSTITUTION - Maki Zaenudin Subarkah; Isti Fatimah Nur Asya Bani (Polteknik Ilmu Pemasyarakatan, 2019)
This study aims to determine the relationship of social support and self esteem towards future orientation in the field of work Andikpas at Class III Bandung LPA. This study is using quantitative with correlational methods design. Determination of the subject (N = 48) in the study used a purposive sampling technique. Data were obtained by modifying the Rosenberg Self Esteem Scale questionnaire made by Rosenberg, the social support questionnaire and the future orientation questionnaire in the field of work created by the researchers themselves from Weiss's social support characteristics and characteristics of future orientation created by Nurmi. The results of this study are: 1) social support among Andikpas friends, self esteem and future orientation in the field of work on Andikpas are in the medium category. 2) The results of the regression test of social support among Andikpas friends towards future orientation in the work field have a significance value of 0.042 which proves that there is a significant influence of the social support variables of Andikpas friends towards future orientation in the field of work on Andikpas. 3) The results of the self esteem regression test towards future orientation in the work field have a significance value of 0.333 which proves that there is no significant effect of the self esteem variable on future orientation in the work field at Andikpas.